2012
DOI: 10.1016/j.seppur.2011.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Fate and seasonal variation of endocrine-disrupting chemicals in a sewage treatment plant with A/A/O process

Abstract: a b s t r a c tThe fate and seasonal variation of several typical endocrine-disrupting chemicals (EDCs), including estrone (E1), 17b-estradiol (E2), 17a-ethinylestradiol (EE2), estriol (E3), bisphenol A (BPA) and 4-nonylphenol (NP), were investigated in a municipal sewage treatment plant (STP) employing an anaerobic/ anoxic/oxic (A/A/O) process located in Beijing, China by monitoring their concentrations in both wastewater and activated sludge in four seasons throughout 2009. Results indicate that in summer, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 34 publications
(43 reference statements)
5
39
0
13
Order By: Relevance
“…Stasinakis et al (2008) reported in influent that almost 45-50 % of phenolic EDCs were found in the particulate phase. During the process of aeration, phenolic EDCs originally adhering to the grits were peeled off due to the agitation of air (Nie et al 2012). But after dealing with vortex-type grit chamber and horizontal flow grit chamber, phenolic EDCs could be removed slightly.…”
Section: Removal Rates Of 14 Edcs In Different Treatment Stages and Tmentioning
confidence: 99%
See 3 more Smart Citations
“…Stasinakis et al (2008) reported in influent that almost 45-50 % of phenolic EDCs were found in the particulate phase. During the process of aeration, phenolic EDCs originally adhering to the grits were peeled off due to the agitation of air (Nie et al 2012). But after dealing with vortex-type grit chamber and horizontal flow grit chamber, phenolic EDCs could be removed slightly.…”
Section: Removal Rates Of 14 Edcs In Different Treatment Stages and Tmentioning
confidence: 99%
“…It has been seriously concerned, in recent years, the negative effects of endocrine disrupting chemicals (EDCs) present in the aquatic environment on wildlife and human around the world (Harries et al 1997;Mills and Chichester 2005;Nie et al 2012;Tsutsumi 2005;Tyler et al 1998). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human and animal excretions constituted the main sources of NEs in the environment, while the occurrence of NEs in municipal wastewater is primarily attributed to human excretions. The occurrence and behavior of NEs in wastewater treatment plants (WWTPs) has been extensively investigated around the world (Hamid and Eskicioglu, 2012;Liu et al, 2009;Nie et al, 2012), but the reported NE removal efficiencies in different WWTPs are largely variable. An important reason for the inconsistencies is that the operational parameters, including temperature, hydraulic retention time (HRT) and sludge retention time (SRT), varied greatly among the different studies.…”
Section: Introductionmentioning
confidence: 99%